2013
DOI: 10.1155/2013/930304
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Stimulation for the Treatment of Pharmacoresistant Nondelusional Auditory Verbal Hallucinations in Dementia

Abstract: Auditory verbal hallucinations (AVHs) are known as a core symptom of schizophrenia, but also occur in a number of other conditions, not least in neurodegenerative disorders such as dementia. In the last decades, Transcranial Magnetic Stimulation (TMS) emerged as a valuable therapeutic approach towards several neurological and psychiatric diseases, including AVHs. Herein we report a case of a seventy-six-years-old woman with vascular-degenerative brain disease, complaining of threatening AVHs. The patient was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
5
0
1
Order By: Relevance
“…29,33,34 We also found 2 case reports. One describing a patient with vascular degenerative disease receiving rTMS, 35 and another a patient with behavioural variant frontotemporal dementia (bvFTD) treated with tDCS. 36…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29,33,34 We also found 2 case reports. One describing a patient with vascular degenerative disease receiving rTMS, 35 and another a patient with behavioural variant frontotemporal dementia (bvFTD) treated with tDCS. 36…”
Section: Search Resultsmentioning
confidence: 99%
“…Regarding hallucinations and delusions, while these are frequent psychopathological manifestations in patients with AD and other dementias, there is a lack of studies to address the potential of noninvasive brain stimulation to treat these symptoms. In a case report, Marras and Palanti have revealed promising results in this area, with findings of a marked reduction of threatening auditory verbal hallucinations after application of high‐frequency temporoparietal rTMS protocol.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the studies in the dementias examined cognitive outcome measures [ 28 ]-[ 42 ] whilst several examined neuropsychiatric symptoms [ 43 ]-[ 45 ]. A total of 13 studies targeted AD patients [ 28 ]-[ 33 ],[ 37 ]-[ 42 ], 4 studies included MCI patients [ 34 ]-[ 36 ],[ 43 ] and 1 study involved DLB patients [ 44 ]. No studies reported the therapeutic use of TMS or tDCS in individuals with VaD, PDD, or FTD.…”
Section: Resultsmentioning
confidence: 99%
“…Typical sites of stimulation included the DLPFC [ 28 ]-[ 31 ],[ 37 ],[ 42 ], temporal regions [ 38 ], temporoparietal regions [ 41 ] or a combination of multiple regions [ 32 ],[ 33 ],[ 39 ]. However, sample sizes were often small (including single-case studies [ 36 ],[ 37 ],[ 43 ]), and the majority were open-label in design. Nevertheless, these studies will help inform future work because several concepts, which are likely to impact upon the utility and effectiveness of non-invasive stimulation, were apparent:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation